Liberalismul și limitele dreptății (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article discusses Michael Sandel’s communitarian critique of John Rawls’s liberal theory of justice. It examines Sandel’s rejection of the priority of justice over the common good and his concept of the situated self, arguing that moral identity is shaped by community, culture, and shared traditions. The article also considers Sandel’s later critique of meritocracy and neoliberal individualism, highlighting the importance of solidarity, civic responsibility, and the common good for sustaining democratic life and social justice. This abstract is generated with artificial intelligence.